Metaphors for Learning: Cognitive acquisition versus social participation - Elmholdt, Claus (Scandinavian Journal of Educational Research, 2003)
This article analyses expressions of cognitive 'acquisition' and social 'participation' metaphors for learning in the practice of support people in an information and communication technology (ICT) company. It is shown that the support peoples' practice is characterised by interplay between the two metaphors that shape learning possibilities and processes of learning. The metaphors are entangled rather then separated, sometimes folded, sometimes coexisting peacefully and sometimes loudly contested and negotiated. The theoretical consequences of these results are discussed, arguing that the metaphors should be seen as complementary rather than mutually exclusive.